Aksesibilitas Keuangan Mikro Syariah dengan Kewirausahaan melalui Pemberdayaan Perempuan Wirausaha Pedesaan - Toto Sukarnoto; Heru Cahyono; abu Lubaba; Muhammad Amin Nurdin; Sri Intan Wulandari (Institute of Research and Community Service at Islamic University of Bunga Bangsa Cirebon, 2024)
Accessibility of financial services is access to financial services in a timely manner, and the adequacy of financing required by economically weaker, low-income groups at an affordable cost. The ability to face various risks with the initiative to create and do new things through the utilisation of resources with the aim of obtaining profits as a consequence. Women no longer only play the role of housewives but have been actively involved in various fields of life, whether social, economic or political. The discussion focuses on the accessibility of Islamic microfinance with entrepreneurship through empowering women as household managers and economic activity capabilities. The research method used in this research is descriptive qualitative research method and data validity is based on triangulation technique. The existence of financing institutions that focus on empowering women microfinance, which has been difficult for entrepreneurs in villages to access capital needs. Through various business assistance activities carried out by sharia-based microfinance institutions, it is very helpful for the growth and development of women microbusiness entrepreneurs through women's empowerment, because the presence of sharia-based microfinance institutions supported by strong capital from the government is very helpful in efforts to achieve the special benefits of empowering women as drivers of economic independence by becoming self-employed women. Keywords: Islamic Microfinance Accessibility, Entrepreneurship, Women's Empowerment Abstrak Aksesibilitas jasa keuangan merupakan akses pada jasa keuangan secara tepat waktu, dan kecukupan pembiayaan yang diperlukan oleh kelompok yang lebih lemah secara ekonomi, berpendapatan rendah dengan biaya yang terjangkau. Kemampuan menghadapi berbagai risiko dengan inisiatif menciptakan dan melakukan hal-hal baru melalui pemanfaatan sumber daya dengan tujuan memperoleh keuntungan sebagai konsekuensinya. Perempuan tidak lagi hanya berperan sebagai ibu rumah tangga tetapi sudah aktif berperan di berbagai bidang kehidupan, baik sosial, ekonomi maupun politik. Pembahasan fokus pada aksesibilitas keuangan mikro syariah dengan kewirausahaan melalui pemberdayaan perempuan sebagai penata kelola rumah tangga dan kemampuan aktifitas ekonomi. Metode penelitian yang digunakan dalam riset ini adalah metode penelitian kualitatif deskriptif dan validitas data dilakukan berdasarkan teknik triangulasi. Keberadaan lembaga pembiayaan yang fokus pada pemberdayaan perempuan melalui pembiayaan mikro sangat berperan meningkatkan tingkat aksesibilitas keuangan mikro syariah yang selama ini wirausaha di desa-desa sulit untuk dapat mengakses kebutuhan permodalan. Melalui berbagai kegiatan usaha pendampingan yang dilakukan lembaga pembiayaan mikro yang berbasis syariah sangat membantu tumbuh kembangnya perempuan wirausaha usaha mikro melalui pemberdayaan perempuan, karena kehadiran lembaga pembiayaan mikro berbasis syariah yang didukung permodalan yang kuat dari pemerintah sangat membantu dalam upaya mencapai kemaslahatan khusus pemberdayaan perempuan sebagai penggerak kemandirian ekonomi dengan menjadi perempuan wirausaha mendiri. Kata Kunci: Aksesibilitas Keuangan Mikro Syariah, Kewirausahaan, Pemberdayaan Perempuan